Worcester Street, ca. 1865-80 - Unknown (Tufts Archival Research Center, 2005)
Street-level view southeast of Worcester Street looking towards Boston City Hospital, located at Harrison Avenue across from Worcester Square. Houses line the northeast side of Worcester Street. The domed roof of the Boston City Hospital Administration Building is visible along the right side of the photograph. Boston City Hospital Administration Building designed by Gridley J.F. Bryant, ca. 1861-65 6 7/8 in diameter (image is round), 7 x 7 overall Photographs